Clinical Concepts and Practical Management Techniques in Dentistry - Moolla, Aneesa (Dentistry, 2022)
Oral healthcare deals with complete oral health, including prevention, treatment, and cure. This book provides readers with the latest updates on dental clinical concepts and practical management techniques. It is divided into four sections that contain in-depth chapters with concepts and techniques from the fields of oral medicine, periodontology, radiology, endodontics, restorative dentistry, dental trauma, and probability and sampling. It is a compendium of work by internationally recognized oral clinicians and public healthcare leaders in dentistry. It presents updates on some of the most pertinent issues within the practice of dentistry, such as regenerative endodontic procedures, the unique role of radiographs, recognition of child abuse, and dental statistics.